2007
DOI: 10.1111/j.1399-6576.2007.01353.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐inflammatory effects of sevoflurane and mild hypothermia in endotoxemic rats

Abstract: Our data suggest that sevoflurane and mild hypothermia attenuate the inflammatory response during endotoxemia in vivo thus contributing to their beneficial role in clinical organ protection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 26 publications
1
40
1
1
Order By: Relevance
“…That this effect has clinical relevance is suggested by the following lines of evidence. First, this anti-inflammatory effect of the volatile anesthetics sevoflurane, isoflurane and desflurane was also demonstrated in animal models of inflammation (6,18,34) and with human cells from healthy donors (35). Second, the inhibitory properties on the IκB· degradation and inducing properties on IκB· protein content occurred at concentrations comparable to those used during sevoflurane or isoflurane inhalation in clinical practice (36).…”
Section: Discussionmentioning
confidence: 99%
“…That this effect has clinical relevance is suggested by the following lines of evidence. First, this anti-inflammatory effect of the volatile anesthetics sevoflurane, isoflurane and desflurane was also demonstrated in animal models of inflammation (6,18,34) and with human cells from healthy donors (35). Second, the inhibitory properties on the IκB· degradation and inducing properties on IκB· protein content occurred at concentrations comparable to those used during sevoflurane or isoflurane inhalation in clinical practice (36).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, cold inhibits the expression of inflammatory mediators; hypothermia inhibits activation of neutrophils and expression of intercellular adhesion molecule-1 (ICAM-1), the adhesion and activation of neutrophils during inflammation (Hanusch et al, 2007). Therefore hypothermia induced expression of the anti-inflammatory cytokines IL-10 (Scumpia et al, 2004); hypothermia attenuates the inflammatory response during WBC, thus contributing to its beneficial role in organ protection (Hofstetter et al, 2007). As elevated serum CK is a characteristic marker of exertional rhabdomyolysis, it may be used for measuring the effects of workload, recovery and possible overtraining.…”
Section: Article In Pressmentioning
confidence: 99%
“…By contrast, postconditioning would be more applicable in a clinical situation. Hofstetter et al (21) examined the postconditioning effect of sevoflurane in an in vivo model of LPS-induced endotoxemia in rats, where administration of sevoflurane 15 min after intravenous injection of LPS resulted in decreased TNF-α and IL-1β. The present study demonstrated that postconditioning is effective even 2 h after LPS stimulation and indicates anesthetic postconditioning could be initiated in a later phase of clinical treatment.…”
Section: A B Cmentioning
confidence: 99%